(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): How or in what way is the excellence of companies in adding value for customers manifested? Purpose: The purpose is to check the results of individual sub-subsets of the selected widget called Adding Value for Clients in two different periods and to compare them Method: The results of selected periods have been used and compared, and we analyse them and, based on the analysis, propose measures for improvements Results: The results show fluctuations in the given building block estimates over the selected period, which may be due to various factors. Organization: With the given suggestions, we influence the improvement of the company’s excellence. By implementing the proposals, we can further improve the value for customers Society: Value added for customers is influenced by all stakeholders in the company - management and employees. It is necessary to be aware that they can only be more successful together and with consistent implementation of measures. Originality: Since the results are also from 2020, it means that these are the latest results of the sub-builders, so we can see the influence of the main factor (Covid 19) on the results Limitations/Future Research: In order to achieve representative results, it would be necessary to compare the results from previous years and analyse the progress / decline in individual subcontractors.